Interplay between CXCR4 and CCR2 regulates bone marrow exit of dendritic cell progenitors - Mariana Pereira da Costa; Carlos M. Minutti; Cécile Piot; Evangelos Giampazolias; Ana Cardoso; Mar Cabeza-Cabrerizo; Neil C. Rogers; Marta Lebrusant-Fernandez; Chrysante S. Iliakis; Andreas Wack; Caetano Reis e Sousa (Cell Reports, 2023)
Summary: Conventional dendritic cells (cDCs) are found in most tissues and play a key role in initiation of immunity. cDCs require constant replenishment from progenitors called pre-cDCs that develop in the bone marrow (BM) and enter the blood circulation to seed all tissues. This process can be markedly accelerated in response to inflammation (emergency cDCpoiesis). Here, we identify two populations of BM pre-cDC marked by differential expression of CXCR4. We show that CXCR4lo cells constitute the migratory pool of BM pre-cDCs, which exits the BM and can be rapidly mobilized during challenge. We further show that exit of CXCR4lo pre-cDCs from BM at steady state is partially dependent on CCR2 and that CCR2 upregulation in response to type I IFN receptor signaling markedly increases efflux during infection with influenza A virus. Our results highlight a fine balance between retention and efflux chemokine cues that regulates steady-state and emergency cDCpoiesis.